The role of livelihood diversification in agricultural modernization among tribal farmers in Bangladesh: A binary logistic model approach. - Anika Tasnim; Jasim Uddin Ahmed; Md Jahangir Alam Khan; Md Abdullah Al-Noman; Arifa Jannat; Md Monirul Islam (PLoS ONE)
This study aimed to evaluate the influence of livelihood diversification on tribal farmers' decision to adopt modern agricultural practices, while also examining the profitability of various agricultural practices and identifying key challenges and policy recommendations for enhancing the sustainability of tribal farming livelihoods in Bangladesh. Data were collected through a structured questionnaire during the month of February 2021 from 115 tribal farmers, followed by a simple random sampling technique. In the study area, only 9.57% of farmers were involved in crop cultivation. The study calculated that human labor cost was the highest in rice production (about 37%). The benefit-cost ratio (BCR) of rice production, livestock rearing, and homestead gardening was estimated at 1.46, 1.41, and 1.09, respectively. Among all agricultural components practiced by the tribal farmers, rice production was more efficient than others. The binary logistic regression findings showed that livelihood diversification, age of the farmers, access to information, household income, and farming experience had a significant influence on the adoption decision of modern agricultural practices. Therefore, promoting livelihood diversification among tribal farmers is crucial for enhancing their resilience and income sustainability. This could include providing training, access to markets, and financial support for activities such as poultry and livestock rearing and non-farm enterprises like homestead gardening.